MOTIF MOON JAE IN DALAM MEREKONSILIASI HUBUNGAN KOREA SELATAN DAN KOREA UTARA MELALUI KOREAN PENINSULA PEACE INITIATIVE - Putri Isnaeni Monday; Hamdan Nafiatur Rosyida (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to discover the motives of Moon Jae In (2017-2022) in issuing the KoreanPeninsula Peace Initiative (KPPI) towards North Korea. Contrary from the previous regime, KPPIemphasized the peace aspect in reconciling relations between the two countries. This research isconducted by descriptive qualitative method, then using the document study method in obtainingsecondary data as a data reference. The results indicate that significant progress of process ofreconciliation between the two countries through the KPPI, which is influenced by the success ofprevious regime of President Roh Moo-Hyun (2003-2008), as well as the ideology of democraticpolitical parties that prioritize pacifism. In addition, South Korea's limited military capacity againstNorth Korea, as well as the influence of Chinese and American powers helped build mutual trustthat became the basis for reconciliation between North Korea and South Korea.